The Impact Of Work Discipline, Leadership Style, Teamwork On Employee Performance Through Satisfaction - Miftachul Mujib; Fery Riyanto; Almira Santi Samasta; Mochammad Eric Suryakencana Wibowo; Dinda Permata Putri (Jurnal Telekomunikasi dan Informatika, 2023)
The aim of this research is to determine the direct and indirect influence of work discipline, leadership style, team collaboration on employee performance through job satisfaction. The motorbike taxis for this research are the State Electricity Company (PLN) Persero Distribution of Central Java and DIY. The population of this research is all PLN employees distribution in Central Java and DIY, totaling 140 employees. The sampling technique used in this research was the census sampling technique which obtained 115 samples. Research data was obtained from questionnaires distributed to respondents. The research method is quantitative using the Structural Equation Model (SEM) using AMOS version 26 software. The research results show that work discipline, collaboration time has a direct effect on employee performance, while leadership style has no direct effect on employee performance. The results further show that work discipline and collaboration time have an indirect effect on employee performance through job satisfaction, whereas leadership style has an indirect effect on employee performance through job satisfaction.